2013
DOI: 10.1097/ftd.0b013e31828e8162
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an LC–MS/MS Method to Measure Tacrolimus in Rat Kidney and Liver Tissue and Its Application to Human Kidney Biopsies

Abstract: The method displayed precision and accuracy suitable for application to TAC measurement in human kidney biopsy tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…In contrast, a poor correlation has been reported between Banff scores and the blood level of TAC (r 2 = 0.0281) [123]. In kidney transplant recipients (two patients) [144], a decrease in TAC was observed in tissue and C 0 whole blood over time (16–300 days) but, there was no correlation between the two measurements.…”
Section: Intratissue Concentrationmentioning
confidence: 99%
“…In contrast, a poor correlation has been reported between Banff scores and the blood level of TAC (r 2 = 0.0281) [123]. In kidney transplant recipients (two patients) [144], a decrease in TAC was observed in tissue and C 0 whole blood over time (16–300 days) but, there was no correlation between the two measurements.…”
Section: Intratissue Concentrationmentioning
confidence: 99%
“…Several assays have been developed for the quantification of the drug in biological samples. The most common methods for routine FK506 monitoring are monoclonal antibody-based immunoassays, while liquid chromatography-tandem mass spectrometry (LC-MS) is currently considered as the reference method [4][5][6][7]. LC-MS provides the most specific routine drug measurement, whereas immunoassays show a notable crossreactivity with inactive metabolites [4,8], especially MIII and MV [9].…”
Section: Introductionmentioning
confidence: 99%
“…CNI-induced nephrotoxicity is likely to be related to intra-renal concentrations of CNIs which may not be properly reflected by whole-blood CNI concentrations. [57][58][59][60] CYP3A5 is the only CYP3A isozyme expressed in the kidney and may limit local exposure to CNIs by intra-renal metabolism. [61,62] Zheng et al [63] demonstrated that Tac concentrations in the renal epithelium of CYP3A5 expressers are 53% lower compared with CYP3A5 non-expressers.…”
Section: Nephrotoxicitymentioning
confidence: 99%